Plant Responses to Hypoxia - Loreti, Elena; Striker, Gustavo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Molecular oxygen deficiency leads to altered cellular metabolism and can dramatically reduce crop productivity. Nearly all crops are negatively affected by a lack of oxygen (hypoxia) due to adverse environmental conditions such as excessive rain and soil waterlogging. Extensive efforts to fully understand how plants sense oxygen deficiency and their ability to respond using different strategies are crucial to increase hypoxia tolerance. Progress in our understanding has been significant in recent years. This topic certainly deserves more attention from the academic community; therefore, we have compiled a series of articles reflecting the advancements made thus far.